2022
DOI: 10.3390/foods11060800
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization and Antioxidant Activity of Yam Polysaccharides

Abstract: This study aimed to characterize the structure of Chinese yam (Dioscoreae Rhizoma) polysaccharide (CYP) and to investigate its protective effect against H2O2-induced oxidative damage in IEC-6 cells. The chemical composition and structural characteristics of the samples were analyzed by chemical and instrumental methods, including high-performance gel permeation chromatography, high-performance anion-exchange chromatography (HPAEC), Fourier transformed infrared (FT-IR), ultraviolet (UV), and scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Flavonoids may play an important role in improving antioxidant capacity, as supplementation of hawthorn‐leaves flavonoids in the diet could improve the activity of antioxidant enzymes (T‐AOC and GSH‐Px) in aged breeder hens (Dai et al, 2021). Moreover, various studies reported that the polysaccharides extracted from Chinese yam by hot water method have the effect of anti‐lipid peroxidation and scavenging hydroxyl radical and superoxide anion radicals, and their antioxidant activity reached the level of vitamin C (Li et al, 2022; Zhou et al, 2021). Antioxidant phenolic compounds extracted from hawthorn were also able to improve antioxidant capacity by increasing the expression of the antioxidant enzymes including SOD, GSH‐Px, and CAT (He et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids may play an important role in improving antioxidant capacity, as supplementation of hawthorn‐leaves flavonoids in the diet could improve the activity of antioxidant enzymes (T‐AOC and GSH‐Px) in aged breeder hens (Dai et al, 2021). Moreover, various studies reported that the polysaccharides extracted from Chinese yam by hot water method have the effect of anti‐lipid peroxidation and scavenging hydroxyl radical and superoxide anion radicals, and their antioxidant activity reached the level of vitamin C (Li et al, 2022; Zhou et al, 2021). Antioxidant phenolic compounds extracted from hawthorn were also able to improve antioxidant capacity by increasing the expression of the antioxidant enzymes including SOD, GSH‐Px, and CAT (He et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The dialyzed solution was lyophilized after secondary alcohol precipitation with anhydrous ethanol to obtain the crude polysaccharide [21,22]. The contents of carbohydrate, uronic acid, and protein were 33.62%, 34.95%, and 5.26%, respectively, and the molecular weight was 20.89 kDa [23].…”
Section: Preparation Of Cypmentioning
confidence: 99%
“…Our preceding study has illustrated that the phosphorylated expression of three proteins, JNK, ERK, and P38, in the MAPK pathway activated by H 2 O 2 was significantly reduced in the presence of CYP, which was able to inhibit the activation of the MAPK pathway [23]. In consequence, to bear out that activating the MAPK signaling pathway in RNA-seq results, ERK inhibitor (PD98059) was added before treating the cells with H 2 O 2 .…”
Section: Effect Of Erk Inhibitor On Mapk Pathway Of H 2 O 2 -Induced ...mentioning
confidence: 99%
“…Chinese yam polysaccharide (CYP) extracted from the Chinese yam , a very popular tuber crop for food and medical purposes in China ( 1 ), has received attention in recent years, owing to its positive nutritional and medicinal characteristics ( 2 5 ). Previous studies have shown that the pharmacological effects of CYP include promoting growth performance, lowering blood glucose and blood lipid, and enhancing anti-oxidation and immunity in animal ( 6 9 ).…”
Section: Introductionmentioning
confidence: 99%